White Matter Injury in Early Brain Injury after Subarachnoid Hemorrhage. Issue 1 (January 2019) - Pang, Jinwei; Peng, Jianhua; Yang, Ping; Kuai, Li; Chen, Ligang; Zhang, John H.; Jiang, Yong
Subarachnoid hemorrhage (SAH) is a major cause of high morbidity, disability, and mortality in the field of neurovascular disease. Most previous SAH studies have focused on improving cerebral blood flow, reducing cerebral vasospasm, reducing neuronal calcium overload, and other treatments. While these studies showed exciting findings in basic science, therapeutic strategies based on the findings have not significantly improved neurological outcomes in patients with SAH. Currently, the only drug proven to effectively reduce the neurological defects of SAH patients is nimodipine. Current advances in imaging technologies in the field of stroke have confirmed that white matter injury (WMI) plays an important role in the prognosis of types of stroke, and suggests that WMI protection is essential for functional recovery and poststroke rehabilitation. However, WMI injury in relation to SAH has remained obscure until recently. An increasing number of studies suggest that the current limitations for SAH treatment are probably linked to overlooked WMI in previous studies that focused only on neurons and gray matter. In this review, we discuss the biology and functions of white matter in the normal brain, and discuss the potential pathophysiology and mechanisms of early brain injury after SAH. Our review demonstrates that WMI encompasses multiple substrates, and, therefore, more than one pharmacological approach is necessary to preserve WMI and prevent neurobehavioral impairment after SAH. Strategies targeting both neuronal injury and WMI may potentially provide a novel future for SAH knowledge and treatment.